PEMAHAMAN GURU TAMAN KANAK-KANAK TENTANG PENGETAHUAN LAYANAN BIMBINGAN KONSELING DAN PELAKSANAAN DI KECAMATAN SOMBA OPU KABUPATEN GOWA - Sri Sofiani; Syamsul Alam Ramli; Eka Poppi Hutami (stit-islamic-village, 2021)
Understanding kindergarten teachers about the knowledge of counseling and implementation guidance services in Somba Opu Subdistrict, Gowa Regency. Problem formulation and this research are how teachers understand guidance and counseling services in schools? and what guidance and counseling services do teachers do in learning?. This research provides an overview of teachers' understanding of guidance and counseling services implemented by teachers in learning in kindergarten. Data collection techniques through interview methods, and questionnaire distribution, as well as documentation. Data analysis in this study was conducted by Data collection, Data reduction, Display data, Data verification. The technique of examination and validity of data is carried out with The Extension of Participation, Perseverance of Questionnaires and Interviews, and Triangulation. The results showed that 20 kindergarten teachers about the understanding of knowledge guidance and counseling services are still lacking and 10 kindergarten teachers have a sufficient understanding of the knowledge of Guidance and Counseling Services. Furthermore, counseling guidance services implemented by teachers in learning in kindergarten are group guidance services, learning guidance, guidance while playing.